Instagram Story: Kajian Hiperrealitas pada Mahasiswa Penggunaan Instagram - Prastiwi, Andar; Chainar, Chainar; Batuallo, Ignasia Debbye (Balale' : Jurnal Antropologi, 2023)
This research describes Instagram Stories which have become a modern lifestyle for students at the Faculty of Social and Political Sciences, Tanjungpura University, Pontianak who are active users of Instagram stories. The type of research used in this research is descriptive research with a qualitative approach. Data collection used in this research was participant observation, distribution of questionnaires, interviews, and documentation. The theory used in this research is Jean Baudrillard's theory of hyperreality, which holds that there is no more reality because in this case what is real is no longer a reference or thing seen by many people. The results of this research show that students when using Instagram carry out the three phases of hyperreality theory to show their self-image through Instagram Stories. Reflecting reality is done by imitating what has been seen from other people's Instagram Stories and then sharing it on Instagram Stories, covering up or misleading reality is done by showing something different on Instagram stories to the actual situation that happened, and covering up absences in reality is done by sharing Instagram A story that seems to be a reality which in reality is used to cover up nothingness.